Digital oxymorons: from ordinary to expressive objects using tiny wireless IMUs - Schlegel, A.; Honnet, C. (Proceedings of the 4th International Conference on Movement Computing, 2017)
In this paper we discuss the potential of ordinary objects acting as human computer interfaces with an Inertial Measurement Unit, the Twiz, to capture a body's orientation and acceleration. The motivation behind this research is to develop a toolkit that enables end users to quickly prototype custom interfaces for artistic expressions through movement. Through an iterative design process we have enhanced existing technical implementations such as wireless data transfer, battery lifespan, two-way communication and data analysis including machine-learning techniques. We conducted object-making sessions and developed software prototypes for audio and visual feedback. We explored a range of experiments related to visual arts, dance, and music by attaching the Twiz to different types of objects to allow users to carry out impromptu interactions. As a result of this process we have gained a better understand of an object's expressive potential whilst capturing and analyzing its movement.